1993
DOI: 10.1021/ic00076a011
|View full text |Cite
|
Sign up to set email alerts
|

New carbon sulfides based on 4,5-dimercapto-1,2-dithiole-3-thione (.beta.-C3S52-): [C3S5]n, C6S8, and C5S7

Abstract: This investigation centers on the preparation of new binary carbon sulfides based on the 1,2-dithiole-3-thione subunit as found in the precursor dithiolate C3S5* 12'. Tricyclic CeSg, 1, was obtained in high yield by thermal elimination of H2S from the dimercaptan J8-C3S5H2. A crystallographic study confirmed a tricyclic structure of idealized D2a symmetry containing an unusual planar 1,4-dithiin unit. The crystals of 1 are monoclinic, space group P2\/c, with a = 8. 046(2), b = 9.797(3), c = 13.818(4) Á, V-1048… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 0 publications
2
21
0
1
Order By: Relevance
“…Selected torsion angles (°): C2-S4-S14-C12 97.8(2), C3-C2-S4-S14 -101.6(4), C13-C12-S14-S4 -97.4(4). C2-S4-S14-C12 -72.52 (14), C3-C2-S4-S14 -79.1(2), C13-C12-S14-S4 -80.4 (2).…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Selected torsion angles (°): C2-S4-S14-C12 97.8(2), C3-C2-S4-S14 -101.6(4), C13-C12-S14-S4 -97.4(4). C2-S4-S14-C12 -72.52 (14), C3-C2-S4-S14 -79.1(2), C13-C12-S14-S4 -80.4 (2).…”
Section: Methodsunclassified
“…1,2-Dithiole-3-thione-4,5-dithiole [1] is a well-known ligand in the coordination chemistry. Additionally, the 1,2-dithiole-4-thione subunit is an interesting precursor to yield binary carbon sulfides as C 5 S 7 or C 6 S 8 [2]. Disulfurization of the bis-methylsubstituted compound furnished a thiodesaurine [3].…”
Section: Introductionmentioning
confidence: 99%
“…A possible intermediate, intraligand S,S 0 -cycloadduct, was not isolated. Rauchfuss et al reported that the reaction of DMAD with the dianionic [M(dmt) 2 ] 2À (M ¼ Zn, Ni (9); dmt ¼ 1,2-dithiol-3-thione-4,5-dithiolate) or with [Cp 2 Ti(dmt)] 0 underwent the cycloaddition at the trithiocarbonate moiety to form the ligand centered cycloadduct (10) [39] (Chart 8 (b)). This reaction is also typical for an organic trithiocarbonate compound with acetylene.…”
Section: 1 Formations Of Interligand and Intraligand Cycloadducts Bmentioning
confidence: 99%
“…In addition, electrophilic acetylene compounds ReC^CeR, where R ¼ CO 2 Me or CO 2 Et, react with 27 [80], 29 [81], 30 [43] or 32 [82] to form the corresponding alkene-bridged adducts (41, 43e45, Scheme 3 (b,c)). In addition, [Cp*Co(dcmedt)] (39), which should be more electron-rich than the Cp complex, reacts with ReC^CeR giving the alkene adduct (42), although the CpCo analog 26 does not produce it well. Diphenylacetylene (PheC^CePh) does not react with those dithiolene complexes.…”
Section: Formation Of Mes Centered Cycloadductmentioning
confidence: 99%
“…However 6 is a 5,5-disulfide rather than the 4,4-disulfide type, 3, we have obtained. Further reported oxidized [dmt] derivatives are a polymeric species [dmt] n , via oxidation of metal salts of [dmt] 2À with SO 2 Cl 2 [11] and a monomeric bis-disulfide, 7, via oxidation with I 2 or TCNQ [12]. No confirmation of the aggregation state of either [dmt] n or 7 however have been given.…”
Section: Introductionmentioning
confidence: 99%